Teaching Math in The Virtual Classroom: Insights And Perspectives - Arrieta, Gilbert; Zulueta, Annie; Lorenzo, Dennis; Gayta, Geliza (FKIP Universitas Lampung, 2021)
This study aims to find out experiences of the math teachers in terms of their preparations, teaching strategies and activities including their insights and realizations in teaching math in the virtual classrooms. The study revealed that student participation and technological capability are their main doubts and concerns in online teaching. It found out that math teachers used more interactive power point presentations, interactive games using gaming websites, and differentiated learning as their teaching strategies and approaches. They realized that teaching math in the virtual classroom is not actually hard, and math teachers should create a new learning environment and be more open-minded in the new normal.Keywords: teaching math online, student participation, online teaching strategies, insights and realizations DOI: http://dx.doi.org/10.23960/jpmipa/v22i2.pp167-178